Parental Involvement and Life Satisfaction in Early Adolescence - Salgado, Mauricio; González, Luis; Yáñez, Alejandra (Frontiers in Psychology, 2021)
Early adolescence is a developmental stage that comprises some basic interactional processes with parents, which can be described as gaining autonomy while maintaining relatedness. Studying how maternal and paternal involvement influence the life satisfaction of sons and daughters during early adolescence is especially important while seeking to understand the challenges of this developmental stage. In this paper, we investigate the differential effects of maternal and paternal involvement, as assessed by sons and daughters, on their life satisfaction during early adolescence. We use a unique survey conducted in Chile, The National Survey on Student Trajectories and Transitions, focusing on a subsample of 497 early adolescents attending 5th to 8th grade (60% female, M age = 12.42, SD = 1.18). Our findings indicate that both paternal and maternal involvement are positively correlated with the life satisfaction of adolescents. We also find that the gender of adolescents moderates the effect of maternal involvement, so daughters (but not sons) who deemed the involvement of their mothers to be more positive reported greater life satisfaction. More positive paternal involvement correlates with greater life satisfaction for sons and daughters. We discuss some mechanisms that might bring about these differences.